Acute pancreatitis induced by acute organophosphate poisoning?. Issue 672 (October 1981) - Moore, P. G.; James, O. F.
Abstract : A 32-year-old male with acute organophosphate poisoning developed hyperglycaemia, glycosuria and ketonuria soon after admission to hospital. Serum amylase estimations suggested a diagnosis of acute pancreatitis. He required insulin therapy to control his hyperglycaemia and the organophosphate poisoning was successfully managed by artificial ventilation, an infusion of pralidoxime and intermittent atropine. He was discharged on the 17th hospital day with no permanent physical sequelae.